Generalized Lorenz-Mie theory of nonlinear optical trapping of core/shell hybrid nanoparticles - Yadav, Sumit; Devi, Anita; De, Arijit Kumar (SPIE, 2022)
In this paper, we present theoretical studies on nonlinear laser trapping of metal/dielectric core/shell nanoparticles using the generalized Lorenz-Mie theory. We discuss the effect of optical nonlinearity under femtosecond pulsed excitation including the effect of Fano-resonance.
Only IISERM authors are available in the record
Keywords: Lorenz-Mie theory; Optical trapping